KURIKULUM MU’ADALAH SEBAGAI PENGUATAN SISTEM PENDIDIKAN PONDOK PESANTREN - Wildan Habibi (Salimiya: Jurnal Studi Ilmu Keagamaan Islam, 2024)
The implementation of the mu’adalah curriculum in the education unit needs intensive guidance from the government. Some madrasas encountered several obstacles in their implementation. The purpose of this study is to determine the application of the mu’adalah curriculum in madrasah Islamiyah darussalamah Islamic boarding school Darussalam Sumbersari Kediri. This madrasah has been implementing the mu’adalah curriculum since 2009 and until now is still consistent in its implementation. The components of curriculum development starting from planning, content / material and evaluation are the main things managed by madrasah as an effort to maintain the existence of the curriculum. The material content of the mu’adalah curriculum Madrasah islamiyah darussalamah using an integral, comprehensive and independent approach. The method used in this study is descriptive qualitative. The results of this study provide a general picture of the success of the implementation of the mu’adalah curriculum is very supported by effective teacher performance meetings are carried out, the formation of a good environment, the relationship between students and supervisors, the availability of facilities and infrastructure of the pesantren environment. The inhibiting factor is some teachers who lack mastery of the material because they have to hold some formal subject matter and the allocation of time is still lacking.